Threshold Potential Simulation on Grounding System using CYMGround Substation Program - FITRIANI, AYU; PANJAITAN, JOEL; SYAHPUTRA, SOFYAN ANWAR; PAKPAHAN, ARNOLD; SIRAIT, REGINA; HUTAJULU, ELFRIDA (Institut Teknologi Nasional, Bandung, 2025)
Excessive fault current on a poor grounding system can cause several symptoms such as the appearance of touch and step voltage and affect the grounding resistance value. This study aims to design a grounding system with variations in the number of conductors and embedded rods where that can have a good impact on the grounding system, which can help reduce the occurrence of excessive fault currents and reduce the value of touch voltage and step voltage that appears. The research method used in this study is the Wenner Method (four-point method) where which method is used in simulating a grounding system that affects the variation in the number of conductors and embedded rods using CYMGRD (CYMGround Substation Program) software. The test results show that the maximum touch voltage value is 729.01 Volts and the maximum step voltage value is 2423.88 Volts. The simulation results state that the condition of the grounding system with variations in the number of conductors and embedded rods is stated in a safe condition.